2019
DOI: 10.1111/ejh.13212
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the complex pathophysiology of sickle cell anaemia and possible treatment

Abstract: Sickle cell anaemia (SCA) is the consequence of abnormal haemoglobin production due to an inherited point mutation in the β‐globin gene. The resulting haemoglobin tetramer is poorly soluble when deoxygenated, and when this is prolonged, intracellular gelation of sickle haemoglobin occurs, followed by haemoglobin polymerisation. If many cycles of sickling and unsickling occur, the red cell membrane will be disrupted leading to haemolysis and vaso‐occlusive events. Recent studies have also shown that leucocyte a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 109 publications
(194 reference statements)
2
68
0
9
Order By: Relevance
“…1 It is also characterized by recurrent vaso-occlusion that involves multicellular adhesions between multiple blood cells, as well as progressive vascular and organ damage. [2][3][4] In the United States (US), SCD is the most common inherited blood disorder, affecting approximately 100,000 patients, and an additional 3.5 million have the sickle cell trait. 1 The population of adult patients with SCD is growing due to early diagnosis of the disease and improved quality of patient care.…”
Section: Introductionmentioning
confidence: 99%
“…1 It is also characterized by recurrent vaso-occlusion that involves multicellular adhesions between multiple blood cells, as well as progressive vascular and organ damage. [2][3][4] In the United States (US), SCD is the most common inherited blood disorder, affecting approximately 100,000 patients, and an additional 3.5 million have the sickle cell trait. 1 The population of adult patients with SCD is growing due to early diagnosis of the disease and improved quality of patient care.…”
Section: Introductionmentioning
confidence: 99%
“…HbS aggregation and polymerization are pivotal primary events leading to the distortion of sickle erythrocyte morphology and presentation of pathophysiologic indicators of SCD (Vekilov 2007;Uzunova et al 2010;Piccin et al 2019). In search of remedies for SCD, using in vitro models, previous empirical studies have demonstrated the capability of varieties of herbal extracts to control and impede HbS aggregation and polymerization (Okpuzor et al 2008;Uwakwe and Nwaoguikpe 2008;Chikezie et al 2010; Chikezie 2011; Imaga 2013; Dash Pauline et al 2013;Nurain et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It implied, therefore, that the physicochemical properties of phytocomponents from the fractionated leaf extracts of A. occidentale, P. guajava, and T. catappa had direct bearing on their capacities to alter the process leading to HbS aggregation and polymerization. Since intra-erythrocytic HbS aggregation and polymerization are pivotal to the pathogenesis and pathophysiology of SCD (Uzunova et al 2010;Piccin et al 2019), the use of chemical agents that covalently modify HbS molecules has been suggested to be an important approach to impede dHbS-M aggregation and polymerization (Park et al 2003;Eaton and Bunn 2017;Kassa et al 2019). Covalent modification of HbS molecules by carbamylation using isothiocyanates, acetylation using methyl acetyl phosphate (MAP), and Snitrosylation of Cys-beta93 has been reported (Xu et al 1999;Park et al 2003;Chikezie, 2011;Jana et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…HU exhibits its clinical benefit through multiple mechanisms, including inducing HbF production, lowering the number of circulating leukocytes and reticulocytes, increasing NO production, and reducing phosphatidylserine exposure. 38 , 39 Given the synergistic effect, pyridoxamine is likely to act distinctly from HU without compromising the beneficial effect, providing evidence that pyridoxamine could be a supplement to HU therapy for patients with SCD.…”
Section: Discussionmentioning
confidence: 99%